CONVECTIVE DRYING KINETICS OF OSMOTICALLY PRE-TREATED POTATO SLICES - Mitrevski, Vangelče (Journal on Processing and Energy in Agriculture, 2021)
In the food industry, convective drying is a widely used method due to his applicability for many food materials. Besides this advantage, convective drying method there are several shortcomings related to the rehydration capacity, low quality of dried material, loss of color, flavour, and important nutrient of the final products. Therefore, the pre-treatment such as blanching, organic acid, and osmotic dehydration before drying is absolutely necessary. Osmotic dehydration is performed to reduce the water content of cell tissues in ingredients such as vegetables and fruits soaked in hypertonic solutions. In this paper the convective drying kinetics of osmotically pre-treated potato slices (variety Carrera) were analyzed. The potato slices were placed in a 300 ml container which containing the osmotic solution and after that the container was placed in the water bath with temperature control. The osmotic pretreatment was carried out with using hypertonic sucrose solutions of 40 oBx sucrose solutions at 40 °C with constant solution flow for 2 hours. Thin-layer drying kinetics of potato slices at four drying air temperatures 40, 50, 60 and 70 °C and two drying air velocities 1 and 2 ms-1 were obtained on the experimental setup designed to imitate an industrial convective dryer. For approximation of the experimental data with regard to the moisture ratio three well known thin-layers drying models from scientific literature and new developed model of Mitrevski et al., were used. The performed statistical analyze show that the model of Mitrevski et al., satisfactorily described the drying behaviour of potato slices.